2001
DOI: 10.1007/s11663-001-0065-z
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of chlorination and microstructural changes of xenotime by carbon tetrachloride

Abstract: Among the rare earth minerals, fluorides, phosphates, and oxides have received attention from the rare earth industry. Traditional methods of decomposition of these minerals, usually alkaline or acid processes, involve several operations. Another possibility to obtain lanthanide chlorides or oxychlorides is reacting the mineral with chlorinating agents, such as gaseous chlorine, hydrogen chloride, thionyl chloride, and carbon tetrachloride, reducing the operation costs and making the process less complicated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…[1], [11], and [12] and mass balance in the reaction system. Estimated values at each experimental condition are also shown in Table VII.…”
Section: E Effect Of Oxychloride Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…[1], [11], and [12] and mass balance in the reaction system. Estimated values at each experimental condition are also shown in Table VII.…”
Section: E Effect Of Oxychloride Formationmentioning
confidence: 99%
“…On the other hand, partial pressure of ZnOCl could be calculated from the present experimental results by using Gibbs energies of Eqs. [1] and [11]. [8] Calculated partial pressure of ZnOCl is also shown in Table VII at each experimental condition.…”
Section: E Effect Of Oxychloride Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, there is general interest in recycling used products containing lanthanide metals and compounds. The conventional process for the extraction of lanthanide elements from oxide ores involves carbochlorination [4], although other chlorinating agents such as HCl and CCl 4 are also being tried [5]. In the conversion of most lanthanide oxides to chlorides, oxychloride phase forms as an intermediate product and controls the kinetics of the reaction, a fact recognized only in the recent literature.…”
Section: Introductionmentioning
confidence: 99%
“…They found that yttrium oxychloride (YOCl) was produced in an intermediary step during the carbochlorination of the xenotime ore, and then the reaction could be followed by a fast step related to the generation of the yttrium trichloride (YCl 3 ). Augusto et al [5] investigated the kinetics of chlorination and microstructural changes of xenotime by carbon tetrachloride at temperatures from 600°C to 900°C. Their results showed that the reaction follows the shrinkingunreacted-core model with formation of a product layer (YOCl), which is chlorinated to give YCl 3 .…”
Section: Introductionmentioning
confidence: 99%